BIOSORPTION OF HEAVY METALS BY ACCLIMATED MICROBIAL SPECIES, ACINETOBACTER BAUMANNII - Singh, Tej Pratap; Goel, Shreyank; Majumder, C.b (Innovare Journal of Life Sciences, 2018)
Objective: The biosorption of the heavy metal species was achieved using the microbial biomass of Acinetobacter baumannii isolated from soil and sludge and further used as bioremediating agent in situ. Material and method: The isolated Acinetobacter baumannii was allowed to grow in synthetic media amended with heavy metal solution. The waste samples, both solid and liquid were collected and chemical parameters was checked viz. pH, temperature, BOD, COD, TDS, chloride and calcium. The heavy metals Cd, Cr, Cu, Mn, Pb, and Zn were determined in liquid waste and industrial wastewater, while metals viz. Cr, Co, Mn, Ni and Zn were measured in the leachate form. Â Result and discussion: The bioremediation of waste was carried out by the biosorption process in a batch process by using the micro-organism, Acinetobacter baumannii. Â Conclusion: It was found that Acinetobacter baumannii reduced Ni by 56% and Cr by 68%., which leads to the conclusion that microbes can tolerate against the heavy metals due to several resistance and catabolic potentials.